Problems of Injustice in College Enrollment and Completion - McPherson, Michael; Baum, Sandy (My University, 2010)
Why does the achievement gap matter? What, if anything, should the government do about it? What should schools, and teachers, do about it? Students are critically examining these questions and more in Professor Harry Brighouse's philosophy seminar, "Education Justice: Theory, Policy and Practice." The achievement gap is one major factor contributing to inequality in college opportunity and outcomes. Serving as distinguished guest lecturers, President McPherson and Professor Baum will contribute to our understanding with scholarly perspectives on issues of fairness in gaining access to college and completing a degree. This effort to open the classroom to the campus community and the public broadly is co-sponsored by the Department of Philosophy.
Keywords: History and Philosophy; Access, Persistence, and Success